The Influence of Non-preventable Risk Factors on the Development of Osteoporosis in Postmenopausal Women - Bijelic, Radojka; Milicevic, Snjezana; Balaban, Jagoda (Materia socio-medica, 2019)
Scientific studies show that many genetic factors can significantly contribute to the onset of osteoporosis in women. The aim of our study was to determine whether non-preventable risk factors (certain genetic predisposition - positive parameters of family and personal history, i.e. family history of osteoporosis, family history of fractures, osteoporotic fractures, previous fractures, menopause duration) can affect the occurrence of osteoporosis in women in postmenopausal age. The study was performed as matched case and controls study. A group of cases consisted of 100 female postmenopausal women in whom by the DEXA method was newly diagnosed osteoporosis at the Clinic for Endocrinology, Diabetes and Metabolism of the University Clinical Center of Republic Srpska during 2015-2016, while the control group consisted of 100 female postmenopausal women without diagnostic signs of osteoporosis. Groups were matched by age (± 2 years). In order to collect demographic data and data on risk factors for osteoporosis and life habits of patients, the Bone Mineral Density Questionnaire for females of the Irish Society for Osteoporosis was used. The results of the univariate logistic regression in our study did not show that early loss of the menstrual cycle before 50 years of age was a significant factor for osteoporosis in postmenopausal women (p=0.421, OR=0.966, 95% CI=0.889-1.051). The analysis of the data of a positive family history of osteoporosis as a risk factor by the model of the multivariate of logistic regression shows that the presence of osteoporosis in close relatives (usually the mother) represents a significant and independent risk factor for the development of osteoporosis (p=0.003, OR=4.567, 95% CI=1.674- 12.460). The results of the study show that the presence of earlier fractures in the tested subjects is a significant independent risk factor for osteoporosis (p=0.015, OR=2.464, 95% CI=1.195-5.084). The results of our study show that the presence of osteoporosis in close relatives (usually the mother) and the existence of previous fractures are significant risk factors for the occurrence of osteoporosis. The presence of these factors may be the reason for the selection of patients for further preventive or curative procedures.